2021
DOI: 10.1111/coa.13754
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of isolated congenital anosmia using simultaneous functional magnetic resonance imaging and olfactory event‐related potentials: Our experience in six patients

Abstract: Olfactory disorders can be classified as conductive, sensorineural or due to an impairment in the olfactory central nervous system. The vast majority of olfactory dysfunction occurs as a result of upper respiratory tract infection (18%-45%), sinonasal disease (7%-56%) or head trauma (8%-20%), whereas the prevalence of primary anosmia is low (0.4%). 1 The causes of primary anosmia are syndromic and non-syndromic. Syndromic primary anosmia is usually associated with Kallmann syndrome, which is characterised by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…However, studies have indicated the discordance of OBV and OERP. Patients with the agenesis of OB may have identifiable OERPs (27)(28)(29). Thus, the olfactory function of these patients may be underestimated for the lack of OERP test.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have indicated the discordance of OBV and OERP. Patients with the agenesis of OB may have identifiable OERPs (27)(28)(29). Thus, the olfactory function of these patients may be underestimated for the lack of OERP test.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Overall, olfactory disorders could be classified as conductive sensory-neural or due to a CNS impairment. 4 Until now, the basic pathogenesis of these complications remains controversial, and evidence suggests that the main pathogenesis of anosmia in the setting of COVID-19 infection can probably depend on CNS dysfunction. 5 The most important current discussions in COVID-19-related anosmia are the controversies about the biochemical basis of these pathologies, diagnosis, and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although most of these anosmic patients will eventually improve within a few months, a considerable number of patients will develop prolonged smell loss more than 2 years after diagnosis 2,3 . Overall, olfactory disorders could be classified as conductive sensory‐neural or due to a CNS impairment 4 . Until now, the basic pathogenesis of these complications remains controversial, and evidence suggests that the main pathogenesis of anosmia in the setting of COVID‐19 infection can probably depend on CNS dysfunction 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Although most of these anosmic patients will eventually improve within a few months, a considerable number of patients will develop prolonged smell loss more than two years after diagnosis 2,3 . Overally, olfactory disorders could be classified as conductive sensory-neural or due to a central nervous system impairment 4 . Until now, the basic pathogenesis of these complications remains controversial, and evidence suggests that the main pathogenesis of anosmia can probably depend on CNS dysfunction 5 .…”
Section: Introductionmentioning
confidence: 99%